Battery impedance measurement using sinusoidal ripple current emulator - Hossain, M.; Islam, Syed; Park, S. (2017)
© 2017 IEEE. This paper presents a sinusoidal ripple current (SRC) emulator which superimposes an ac ripple current frequency into a dc charging current in order to produce a sinusoidal ripple current without a ripple current controller. It can be used for several purposes:1) to analyze the impact of ac ripple current magnitude and frequency on the battery internal characteristics; 2) to determine the parameters related to thermal rise and lithium plating; 3) to obtain more updated parameter information for improved utilization of a battery; 4) to determine the optimal ripple current frequency at the minimum impedance point by sweeping the ripple current frequency; 5) to utilize the obtained impedance data for estimating the battery circuit parameters and SOC level. The internal characteristics of batteries are complex and dynamic; therefore, it is beneficial to use the SRC emulator to validate SRC performance in a battery stack before integrating a SRC algorithm into a battery charger. This paper describes the development procedure of a SRC emulator to produce the electrochemical impedance spectroscopy (EIS) measurement for measuring the battery internal impedance. In order to validate the performance of the SRC emulator, a 12.8 V, 40 Ah Li-ion battery was charged at C/8 rate in CC mode with ± 1 App ac ripple current perturbation with an impedance from 20 Hz to 2 kHz.